Tunable Electromagnetically Induced Transparency-Like in Graphene metasurfaces and its Application as a Refractive Index Sensor - Jia, Zhongpeng; Huang, Li; Su, Jiangbin; Tang, Bin (Journal of lightwave technology, 2021)
We present numerical and theoretical analysis of the tunable electromagnetically induced transparency-like (EIT-like) effect based on graphene metasurfaces. The unit cells of metasurfaces are composed of a pair of parallel graphene strips and a two-split rectangular graphene ring resonator, both of which are performed as bright modes. The physical mechanism behind the EIT-like effect results from the frequency detuning and hybridization coupling of two bright modes. The FDTD simulation results show an excellent agreement with the theoretical analysis based on the coupled Lorentz oscillators model. Moreover, the transparency window of EIT-like effect can be modulated not only by changing the geometry of the nanostructure, but also by adjusting the Fermi level of graphene, allowing for an actively tunable group time delay of the light. In addition, owing to the peak frequency of the transparency window is highly sensitive to the variation of refractive index of the surrounding media, we demonstrate a refractive index sensor with sensitivity of ∼ 6800 nm/RIU, and the calculated FOM can reach up to about 14.2. Therefore, our proposed nanostructure provides a feasible platform for slow light and sensing applications.